Correlation between the height of the flight curve and the length of the jump at the Planica Ski Flying Competitions in 2009, 2010 and 2013 - Vodicar, J.; Ulaga, B.; Jost, B. (Sciene and nordic skiing III, 2016)
Ski flying is an interesting and exciting sport. The competitions held at the world`s largest hills attract massive crowds of spectators and viewers, and ski jumpers are able to fly over the 250-meter mark. However, in order to see jumps of such length we will gradually need to construct slopes which are considerably bigger than existing ski flying hills (Joßt, Coh & Vodicar, 2013). The increase in hill size will affect the flight curve (Müller, 1997), which characteristically defines the angle of the flight path from the beginning of the jump to its end. In order to construct larger hills, the flight curve will have to be studied in detail for each point of the flight. The height of the curve can be affected by a number of factors (geometric characteristics of the slope profile, ski jumping/flight technique, aerodynamic factors, weather conditions, and the morphological features of the ski jumper). In the past, the body weight of a ski jumper was identified as one of the main factors determining the aerodynamics of the flight (Schmölzer & Muller, 2002). The jumping technique of ski jumpers is importantly affected by aerodynamic forces on the slope (Norstrud, 2008; Virmavirta et al., 2005), as well as by the ski jumpers' equipment. In recent years, permitted jump suit sizes changed frequently (from + 6cm in the 2012/2013 season, to + 2cm in the 2012/2013 season, and + 4cm in the 2014/2015 season). Ski jumpers raised the issue of smaller jump suits, claiming that, as a result of poorer aerodynamic efficiency, these suits negatively affected their flying sensations and increased the risk of falls during landing, as particularly evident in the long jumps past the hill size point. The aim of this study was to identify the changes in the flight curve which were potentially caused by smaller jump suits in 2012/2013, primarily to determine the correlation between the height of the flying curve and the length of the jump at World Cup Finals in 2008/2009 and 2012/2013, and at the 2010 Planica Ski Flying World Championship. The second objective of the study was to establish the correlation between jump length at the 2012/2013 Planica Ski Jumping World Cup Final and four independent factors which importantly define jump length (in-run speed, flying height at 112 m point, aerodynamic index of flying, and wind speed).